SPK: Analisa Metode AHP Pada Guru Berprestasi di SD 095130 Senio Bangun - Parhusip, Friskila; Yustika, Asri; Syahputri, Indah; Damanik, Nila Soraya (MEANS (Media Informasi Analisa dan Sistem), 2018)
This decision support system is used to select outstanding teachers and is aimed at SD 095130 Senio Bangun which still uses manual system in assessing the candidates of outstanding teachers. So this system is expected to assist the agency in the process of assessment and determination of outstanding teachers in the area of Pematang Siantar City quickly and accurately. The method used in ranking the selection of teachers achieving achievement in this system using AHP method is a method The workings of this method is almost similar to the workings of the brain, namely by elaborating complex problems into more problems that are more structured and systematic. Where alternatives are used as much 4 teachers with job criteria, education, rank / goals / Space and last sk. The results of ranking in this system are influenced by the selection of preference criteria and determinations entered into the system. The test of this system uses data from 45 teachers, ranking divided according to Kindergarten, SD / MI, SMP / Tsanawiyah, SMA / MA, and SMK. Of the several trials that have been done to determine the achieving teacher, the ranking results are much faster and more accountable.